Curcumin Targets p53-Fibrinolytic System in TGF-β1 Mediated Alveolar Epithelial Mesenchymal Transition in Alveolar Epithelial Cells - Shaikh, Sadiya B.; Prabhu, Ashwini; Bhandary, Yashodhar P. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Aims: We aim to investigate curcumin interaction with p53-fibrinolytic system, smad dependent and independent pathways underlying their prime role during lung injury and fibrosis. Background: Curcumin, an active component of Curcuma longa plant, substantially modulates respiratory conditions. TGF-β1 plays a central role in lung remodeling by balancing extracellular matrix (ECM) production and degradation, which is a hallmark for alveolar EMT. However, the crosstalk of curcumin is not known yet with TGF- β1 mediated p53-Fibrinolytic system regulating alveolar EMT leading to IPF. In the present study, the potential molecular mechanism of curcumin in TGF-β1 mediated p53-fibrinolytic system in basal alveolar epithelial cells was explored. Objectives: To understand the potential molecular mechanism of curcumin in TGF-β1 mediated p53-fibrinolytic system in basal alveolar epithelial cells. Methods: Basal alveolar epithelial cells were treated with TGF- β1 to induce alveolar EMT and after 24 hrs curcumin was administered to study its anti-fibrotic effects. Molecular techniques like immunoblot, RT-PCR and immunofluorescence were performed to assess the anti-fibrotic role of curcumin on EMT markers, IL-17A, p53-smad interaction to investigate the anti-fibrotic role of curcumin. Results: The results indicated that TGF-β1-induced EMT in A549 cells exhibited altered expression of the IL-17A, p53-fibrinolytic markers and EMT markers at the mRNA and protein level. Intervention with curcumin attenuated alveolar EMT and inactivated TGF-β1 induced Smad/non Smad signaling pathways via blocking p53-fibrinolytic system. Conclusion: This study provides the first evidence of the dynamic response of curcumin on TGF- β1 mediated p53-fibrinolytic system during alveolar injury in vitro.
Keywords: Smad/non-smad proteins